Sequential Loss of LC Noradrenergic and Dopaminergic Neurons Results in a Correlation of Dopaminergic Neuronal Number to Striatal Dopamine Concentration - Szot, Patricia; Franklin, Allyn; Sikkema, Carl; Wilkinson, Charles W.; Raskind, Murray A. (Frontiers in Pharmacology, 2012)
Noradrenergic neurons in the locus coeruleus (LC) are significantly reduced in Parkinson’s disease (PD) and the LC exhibits neuropathological changes early in the disease process. It has been suggested that a loss of LC neurons can enhance the susceptibility of dopaminergic neurons to damage. To determine if LC noradrenergic innervation protects dopaminergic neurons from damage, the dopaminergic neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) was administered to adult male C57Bl/6 mice 3 days after bilateral LC administration of 6-hydroxydopamine (6OHDA), a time when there is a significant reduction in LC neuronal number and innervation to forebrain regions. To assess if LC loss can affect dopaminergic loss 4 groups of animals were studied: control, 6OHDA, MPTP and 6OHDA + MPTP; animals sacrificed 3 weeks after MPTP administration. The number of dopaminergic neurons in the substantia nigra (SN) and ventral tegmental area (VTA), and noradrenergic neurons in the LC were determined. Catecholamine levels in striatum were measured by HPLC. The loss of LC neurons did not affect the number of dopaminergic neurons in the SN and VTA compared to control; however, LC 6OHDA significantly reduced striatal dopamine (DA) (29% reduced) but not norepinephrine (NE) concentration. MPTP significantly reduced SN and VTA neuronal number and DA concentration in the striatum compared to control; however, there was not a correlation of striatal DA concentration with SN or VTA neuronal number. Administration of 6OHDA prior to MPTP did not enhance MPTP-induced damage despite an effect of LC loss on striatal DA concentration. However, the loss of LC neurons before MPTP resulted now in a correlation between SN and VTA neuronal number to striatal DA concentration. These results demonstrate that the loss of either LC or DA neurons can affect the function of each others systems, indicating the importance of both the noradrenergic and dopaminergic system in PD.